Assessment of students anxiety level and technology readiness in a simulation-based obstetrics training - ÇATAR, RAMAZAN ÖZGÜR; KİTAPÇI, OKAN CEM; ŞİŞMAN KİTAPÇI, NUR; DEMİRGÖZ BAL, MELTEM; MUMCU, GONCA (My University, 2023)
Aim: This study aims to evaluate the effects of simulation-based obstetrics training on students' professional development and examine students' anxiety and technology readiness. Material and Methods: The study was quasi-experimental and performed with 3rd -year students in Midwifery Department (n=60) between September 2018 and January 2019. Students attended a 14-week simulation-based delivery training. In the pre-and posttraining periods, the data were collected by the State-Trait Anxiety Inventory (STAI) and the Tendency Scale for the Use of Technology. Results: Students reported that simulation-based delivery training improved their "professional skills" (95%) and "professional internalization" (93.4%). They stated that there was a positive effect on "anxiety in the working environment" (93.3%) in posttraining. Since no significant differences were observed in scores of the Tendency Scale for the Use of Technology and STAI in pre-and post-training periods (p>0.05), it was thought that they were not potential barrier factors in the training. Conclusion: The ensuring of professional development was achieved by using simulation-based training in the study. However, technology readiness and anxiety levels were stable in pre-and post-training periods

Simülasyona Dayalı Doğum Eğitimi Uygulanmasında Öğrencilerin Kaygı Durumları ve Teknolojik Hazırbulunuşluklarının İncelenmesi Amaç: Bu çalışmanın amacı, simülasyona dayalı normal doğum dersinin öğrencilerin mesleki gelişimleri üzerindeki etkilerini değerlendirmek ve öğrencilerin kaygı durumları ile teknolojiye hazır bulunuşluk durumlarını incelemektir. Gereç ve Yöntem: Araştırma yarı deneysel bir çalışma olup Eylül 2018-Ocak 2019 tarihleri arasında Marmara Üniversitesi Ebelik Bölümü üçüncü sınıf öğrencileri (n=60) ile yürütülmüştür. Öğrenciler, gerçek hayat senaryolarını kapsayan 14 haftalık simülasyona dayalı normal doğum dersine katılmıştır. Veriler, eğitim öncesi ve sonrası dönemde Durumluk-Sürekli Kaygı Envanteri (STAI) ve Derste Teknoloji Kullanımına Yönelik Eğilim Ölçeği ile değerlendirilmiştir. Bulgular: Öğrenciler, simulasyona dayalı normal doğum eğitiminin, “mesleki becerilerini” (%95) ve “mesleği içselleştirmelerini” (%93.4) geliştirdiğini bildirmiştir. Eğitim sonrasında “çalışma ortamındaki kaygı” (%93.3) durumuna yönelik olumlu gelişme olduğunu belirtmişlerdir. Eğitim öncesi ve sonrasında; Derste Teknoloji Kullanımına Yönelik Eğilim Ölçeği puanı ile Durumluk-Sürekli Kaygı Envanteri (STAI) puanı arasında fark tespit edilmemiştir ve bu eğitim için olası engelleyici faktörler olmadıkları görülmüştür (p>0.05). Sonuç: Çalışmada simülasyona dayalı normal doğum eğitiminin mesleki gelişime katkı sağladığı bulunmuştur. Ayrıca, teknolojiye hazırbulunuşluk ve kaygı düzeylerinin eğitim öncesi ve sonrası benzer düzeyde olduğu saptanmıştır.
Keywords: Anxiety; professional development; simulation-based education; use of technology; Kaygı; mesleki gelişim; simülasyona dayalı eğitim; teknoloji kullanım